Identification of hypocrealean reptile pathogenic isolates with MALDI-TOF MS. (16th November 2018) - Schneider, Juliane; Heydel, Tilo; Pees, Michael; Schrödl, Wieland; Schmidt, Volker
Abstract: Biotyper analysis of Nannizziopsis guarroi, a fatal fungal pathogen in lizards, was described recently. Hypocrealean fungal infections in captive reptiles appear with an increasing frequency during the last decade. Therefore, the aim of this study was to proof Matrix-assisted laser desorption ionization-time-of-flight mass spectrometry (MALDI-TOF MS) as diagnostic tool for the identification of reptile pathogenic hypocrealean fungi. Ten fungal isolates obtained from nine reptiles with fungal glossitis, disseminated visceral mycosis, pneumomycosis, and fungal keratitis were analyzed. Phylogeny consisted of fragments of the large subunit of nuclear encoded ribosomal DNA (D1/D2, LSU) and the internal transcribed spacer region 1 of nuclear encoded ribosomal DNA (ITS1) as well as the protein coding gene translation elongation factor 1 alpha (TEF). Results revealed unanimously two Metarhizium granulomatis genotypes in a total of three isolates, various M. viride genotypes ( n = 3), two different Purpureocillium lilacinum isolates as well as one isolate of each P. lavendulum and Beauveria bassiana. Purpureocillium lilacinum and B. bassiana are likewise frequently employed as a mycoinsecticide and mycoacaricide in agriculture on a worldwide scale and have occasionally been reported in man, causing fungal keratitis, sclerokeratitis, nosocomial infections in immunosuppressed patients, as well as cavitary pulmonary disease and cutaneous hyalohyphomycosis in immunocompetent patients. According to the results establishment of Biotyper analysis for faster differentiation of reptile-associated fungal pathogens is entirely justified.